A Review: Modern Blind Stick - Shreyas Chudiwale; Nilesh Patil; Jayesh Mahajan (Journal of Electronic Design Engineering, 2022)
The studies awareness on an easy method of identifying the barrier and direction by way of employing an ultrasonic sensor that could hit upon a hole or stair with a maximum range of around 2 meters. As we will see, blind people are having issue going approximately their daily lives because they’re not able to peer even a single factor. The research makes a specialty of an easy technique of figuring out the barrier and path through employing an ultrasonic sensor which could locate a hollow or stair with a most range of round 2 meters. As we can see, blind people are having issue going approximately their everyday lives due to the fact they’re unable to peer even an unmarried component. With our idea, we are hoping to assist people like these in living their lives freely. This sophisticated blind stick has some of features to be able to certainly aid blind people in navigating routes and detecting limitations, making their day by day lives less difficult.